Growth differentiation factor 15 – a review of current literature on biological roles and clinical significance - Rzemieniewski, Bartosz; Kasztelan, Aleksandra; Poboży, Kamil; Domańska-Poboża, Julia (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Growth differentiation factor 15 (GDF15), a member of the TGF-β superfamily, plays crucial roles in various physiological and pathological processes including inflammation, apoptosis, angiogenesis, cell repair, growth, metabolic regulation, and immune response. This review aims to discuss the biological roles and clinical significance of GDF15 and to analyze its impact across different medical fields such as cardiology, oncology, neurology, gynecology, and areas related to aging and metabolic disorders. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A review was constructed through a literature search on PubMed and Google Scholar databases, focusing on studies from 2014 to 2024, using relevant keywords. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Analysis of the literature. Recent research highlights GDF15’s potential as a biomarker in cardiovascular diseases, its role in cancer progression and resistance to therapies, and its significance in metabolic regulation affecting conditions like obesity, diabetes, and cachexia. Emerging research also points to its role in aging, mitochondrial diseases, and systemic conditions such as sepsis, liver, and lung disorders. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. GDF15’s involvement in multiple pathological states and its broad impact across various medical disciplines underline its potential for future clinical applications. Understanding GDF15’s complex roles could lead to novel therapeutic strategies and enhance prognostic assessments in diverse medical fields.